A transcriptome-wide association study identifies novel susceptibility genes for psoriasis. Issue 2 (18th August 2021) - Zhu, Dongli; Yao, Shi; Wu, Hao; Ke, Xin; Zhou, Xiaorong; Geng, Songmei; Dong, Shanshan; Chen, Hao; Yang, Tielin; Cheng, Ying; Guo, Yan
Abstract: Although >80 psoriasis genetic risk loci have been reported through genome-wide association studies (GWASs), the genetic mechanism of psoriasis remains unclear. To identify novel candidate genes associated with psoriasis and reveal the potential effects of genetic factors in the development of psoriasis, we conducted a transcriptome-wide association study (TWAS) based on summary statistics from GWAS of psoriasis (5175 cases and 447 089 controls) and gene expression levels from six tissues datasets (blood and skin). We identified 11 conditionally independent genes for psoriasis after Bonferroni corrections, such as the most significant genes UBLCP1 ( P YFS = 2.98 × 10 −16 ) and LCE3C ( P SNSE = 9.72 × 10 −12, P SSE = 6.24 × 10 −12 ). The omnibus test identified additional five genes associated with psoriasis via the joint association model from multiple reference tissues. Among the 16 identified genes, 5 genes ( CTSW, E1F1AD, KLRC3, FIBP and EFEMP2 ) were regarded as novel genes for psoriasis. We evaluated the 16 candidate genes by querying public databases and identified 11 differentially expressed genes and 8 genes proved by the knockout mice models. Through GO enrichment analyses, we found that TWAS genes were enriched in the known GO terms associated with skin development, such as cornified envelope ( P = 4.80 × 10 −8 ) and peptide cross-linking ( P = 1.50 × 10 −7 ). Taken together, our results detected multiple novel candidate genes for psoriasis, providing clues for understanding the genetic mechanism of psoriasis.